Tipología del doble en el relato fantástico peruano en el siglo XX y principios del siglo XXI a partir del análisis de la obra de Clemente Palma, José B. Adolph y Carlos Calderón Fajardo - Vega Mora, Max Ivo (2024)
The purpose of this doctoral research is to offer a detailed classification of the Peruvian fantastic double. For this purpose, a corpus composed of narratives by Clemente Palma, José B. Adolph and Carlos Calderón Fajardo has been chosen. Authors chosen because: they are representative figures of Peruvian fantastic literature; being considered insular –whose works have been little studied until today–; and, for representing three different periods of non-mimetic narrative in the country (Palma's work is set in the early years of the 20th century, Adolph's work –his most important work– in the 60s and 70s of the same century and that of Calderón Fajardo in the early years of the 21st century). These temporal distinctions will also allow us to view fantastic literature from the three paradigms of the genre: classic fantastic, modern fantastic and postmodern fantastic. In this way, the analysis begins with how the theme of the double is presented and how it operates in the classic fantastic (through the examination of Palma's work). Next, how the theme of the double is presented and how it operates in modern fantastic (through an examination of Adolph's work). Finally, how the theme of the double is presented and how it operates in the postmodern fantastic (through an examination of Calderón Fajardo's work). The chapters will show that the doubles of these works are determined by modalities, types and processes stipulated by the theory, which, effectively, account for an evolution of the theme in Peruvian fantastic. We will also observe that these modalities are determined, in turn, by the paradigm of the fantastic to which they belong. Finally, a typology of the Peruvian fantastic double will be offered based on: the different ways in which the protagonist subject (who suffers duplication in most cases) sees his objective reality disrupted; the respective modality; and, the essential characteristics of each of the doubles analyzed.